TINGKAT KELANGSUNGAN HIDUP DAN RASIO KONVERSI PAKAN PADA BUDIDAYA IKAN GURAMI (Osphronemus goramy LAC.) DENGAN SISTEM BIOFLOK DAN PEMBERIAN PAKAN KADAR PROTEIN YANG BERBEDA - wijayanti, retno; muarif, muarif; lesmana, dudi (JURNAL MINA SAINS, 2019)
This research was carried out on March to August, 2018, and the experiment on April to June, 2018 at the Fishery Laboratory, Djuanda University Bogor. The objective of research is to know and analyze the survival rate and feed conversion ratio of Giant Gouramy that cultured on biofloc media and different protein levels. The experimental design that used is completely randomized design with 2 treatments and 6 replications. The treatments are treatment A (feeding of protein level of 17% + mollase addition with C,/N ratio 12) and treatment B (feeding of protein level of 30% without mollase) Fish that used is Giant Gouramy fry with length 5-7 cm that maintained cylinder container of diameter 1 m and height 1 m. The results of research that the artificial feeding of protein level of 17% + mollase addition with C/N ratio 12 gives the survival rate which is better, but the feed conversion ratio is bad. The average of the highest survival rate of Giant Gouramy is 89% (treatment A) and the low feed conversion ratio is 1.6 (treatment B). Water quality during the research are temperature of 23,6-30,0 °C, dissolved oxygen of 6.4- 8.8 mg/l and pH of 6,3-8,8. Key words: Giant Gouramy, biofloc, feed conversion ratio, protein level.